The Prevalence of Dysphagia among in-Patients in Educational Hospitals of Ahvaz in the Second Half of 2010 - Peyman Zamani (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background & Objective: Dysphagia refers to any disturbance in movement of food bolus from mouth to stomach that is due to neurological motor disorder of swallowing processes. Since, a speech and language pathologist is an active member of the medical team assessing and treating patients with dysphagia, knowledge of basic information about prevalence and etiology of dysphagia seems necessary for planning of rehabilitation programs.Subjects & Methods: In this retrospective descriptive study, 1860 medical profiles of hospitalized patients of educational hospitals in the city of Ahvaz were randomly selected. By the use of NDPCS checklist, data regarding existence or nonexistence of dysphagia, etiology of dysphagia, prevalence of dysphagia in different age and sex, accompanying speech disorders, and prevalence of dysphagia in different wards of the studied hospitals were recorded and entered into SPSS software for analysis.Results: 4.2% of total patients had dysphagia (4% male, 4.5% female). No significant difference was observed between sexes regarding prevalence of dysphagia (P>0.05). Neurologic diseases were the most frequent causes of dysphagia. Males aged between 0-10 years had the highest dysphagia rate. The highest and lowest dysphagia rates were observed in neurology ward and internal medicine ward of the studied hospitals.Conclusion: The finding of this study suggest that speech therapists to pay more attention to age, common etiology and hospital wards with higher dysphagia rate and it is recommended to use early interventions for dysphagia.